208 Developing future leaders through quality improvement-themed webinars. (16th November 2020) - Fukui, Akiko
Abstract : Quality Improvement (QI) and leadership are increasingly acknowledged as basic training requirements across all healthcare professions. While UK medical schools are increasingly incorporating QI teaching into the undergraduate curricula, training opportunity is still limited for most healthcare students. IHI St George's is an interdisciplinary student organisation that is a part of Institute for Healthcare Improvement (IHI) Open School network and is aimed at filling the gaps in the undergraduate curricula on QI. The aim of the study was to educate and inspire healthcare students to participate in improvement projects. Our objectives were 1) to assess students' baseline preparedness in conducting QI, 2) to design webinar series based on the feedback, and 3) to assess the effectiveness of webinars in teaching QI basics. Methods: Two webinar sessions were delivered live by junior doctors and recorded. Links to pre-and post-survey forms on Google Forms were sent to all attendees before and after the delivery of webinar session in September 2020. the topics covered the basic principles of QI, how to collect and analyse the data, and how to publish the results, with the focus on the speakers' personal experiences. Results: The pre-series survey was completed by 36 attendees out of 51 participants. All participants were affiliated with a healthcare course. 92% (n=33) indicated their interest in QI/leadership but 83% (n=30) reported to have never participated in any QI projects before and 78% (n=28) reporting minimal or no confidence with applying QI techniques in practice. The main barriers to carrying out a project were the lack of knowledge (81%, n=29), support (50%, n=18) and time (33%, n=12). The results from our interim survey demonstrates student's interests in QI as well as the lack of exposures to QI training and projects. Short webinars focusing on educating as well as inspiring healthcare students can help introduce QI to the future healthcare leaders.